Color coulomb potential in Yang-Mills theory from Hamiltonian flows - Leder, Markus; Pawlowski, Jan M. (Arxiv, 2011)
We consider the Hamiltonian formulation of Yang-Mills theory in the Coulomb gauge and apply the recently developed technique of Hamiltonian flows. We formulate a flow equation for the color Coulomb potential which allows for a scaling solution that results in an almost linearly rising confining potential.